Dialectics of Production Relations from Industry 1.0 to 5.0: An Analysis from Marxist-Leninist and PMPD Perspectives - Rimal, Bishnu (State, Society and Development: PMPD Perspectives, 2025)
This article explores the historical and contemporary transformations in modes of production, class structures, and labor relations from Industry 1.0 to Industry 5.0 through the analytical lens of Marxist–Leninist theory and People’s Multiparty Democracy (PMPD). It builds on Karl Marx’s foundational premise that the aim of philosophy is not merely to interpret the world but to change it, applying this praxis-oriented ethos to the analysis of capitalist development, class struggle, and systemic transformation. Drawing on Marx’s theory of historical materialism, Lenin’s theory of imperialism, Mao’s concept of New Democracy, and Bhandari’s creative adaptation of Marxism–Leninism through PMPD, the study synthesizes these theoretical frameworks to examine how evolving socio-economic conditions shape and reshape production relations and labor dynamics. Based on the literature and contributions of Bhandari, this article underscores a dialectical interplay between politics, law, and the economic base, emphasizing that political movements both reflect and influence changes in production systems. The analysis reveals that revolutions—democratic or socialist—are context-specific responses to exploitative structures and that legal and institutional changes are required to consolidate socio-economic transformations. This theoretical study, enriched with empirical references, highlights the importance of linking revolutionary ideology to practical, participatory frameworks like PMPD, especially in peripheral nations such as Nepal.